Poetic Protest and Testimony in Endsars Rhythms - Jayne I. Owan; Onyekachi Peter Onuoha (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
Art participates in social movements and resistance to police brutality by virtue of poetic protest & testimony. Political corruption and police brutality is a vector for resistance and poetic testimony in African society. I conduct a textual analysis of a digital memorial to understand the ways Poetic Protest and Testimony in Endsars Rhythms. This study through the application of the concepts of protest and testimony observes that EndSARS Rhythms through poetic frame participates in preserving memory within the structure of art and documenting the exploitation and brutality of the youth by the Nigeria Police Force. It submits that EndSARS Rhythms is poetic protest and testimony to police brutality. This paper claims that EndsSARS Rhythm is a literary testimony for victims of police brutality and survivals in Nigeria.